The Effect of Self-Care Management Intervention on Hardiness in Type 2 Diabetes Mellitus Patients - Kurniadi Kurniadi; Sukmawati; Syarief Suwardhin; Supriadin (Pascasarjana, Mataram University, 2026)
Type 2 diabetes mellitus (T2DM) requires continuous self-care management and has the potential to impact psychological outcomes such as hardiness. This study aims to analyze the effect of self-care management interventions on hardiness in T2DM patients. The design used was a quasi-experimental pretest–posttest with a non-randomized control group at 3 community health centers in Bima City (August–October 2025). A purposive sample of 100 T2DM patients was divided into treatment (n=50) and control (n=50) groups. The intervention was a structured self-care management education program (diet, physical activity, medication adherence, glucose monitoring, foot care, stress management, and problem-solving). Hardiness was measured before and after the intervention and analyzed using the Wilcoxon test. Descriptively, the proportion of “good” hardiness in the treatment group increased from 6% to 80%, while in the control group decreased from 28% to 24%. The Wilcoxon test showed a significant increase in hardiness in the treatment group (Z=−6.083; p<0.001) and no significant increase in the control group (Z=−0.632; p=0.527). These findings support the effectiveness of self-care management interventions in improving hardiness in T2DM patients, with the potential for confounding by differences in baseline characteristics between groups (age and duration of DM).